Calculation approach for current–potential behaviour during pulse electrodeposition based on double-layer characteristics. (November 2014) - Scharf, I.; Sieber, M.; Lampke, T.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper introduces a phenomenological calculation approach for the electrolytic pulse deposition of nickel under high polarisation based on an equivalent electrical circuit. In a quasistationary state of the deposition, the electrolyte resistance and double layer parameters are identified by electrochemical impedance spectroscopy and galvanostatic polarisation. The charge–transfer resistance of both the anodic and cathodic electrode double layer is inversely proportional to the current density. This means the overpotentials over the electrode double layers are independent of the current density. For short pulse on-times and off-times (up to 10 ms), the behaviour of the electrolytic cell is mainly determined by the double layer characteristics and the calculation approach therefore allows the prediction of the current–potential behaviour during pulse deposition under high polarisation. For larger pulse widths, the time-dependent evolution of the overpotentials occurring at the electrode/electrolyte interface becomes a determining factor for the cell potential.